Economic Growth, Innovation, Cultural Diversity. What Are We All Talking About? A Critical Survey of the State-of-the-art - Carole Juliette Maignan; Gianmarco Ottaviano; Dino Pinelli (Fondazione Eni Enrico Mattei (FEEM), 2003)
This report constitutes the first deliverable of the project ENGIME Economic Growth and Innovation in Multicultural Environments, financed by the European Commission FP5 Key Action: Improving socio-economic knowledge base. Contract HPSE-CT2001-50007
Keywords: Z10; 330; Multiculturalism; Diversity; Economic Growth; Entwicklung; Wirtschaftswachstum; Innovation; Kultur; Kommunikation; Institutionenökonomik; Globalisierung; Sozialkapital; Theorie